The role of China's 'one belt one road initiative' project in interdependence relations between China and Africa: the case of Ethiopia and South Africa from 1994 to 2019 - Yildiz, Fatma (African Studies, 2025)
China often claims that its presence in Africa is one of solidarity with previous liberation struggles and post-independence countries trying to remove the remnants of colonialism's shackles. Indeed their developmental role, it is claimed, is to achieve this end through a relationship of respect for the sovereignty of states and equality of political relationships and economic development objectives. This study delves into the asymmetrical interdependence relations between China and African countries, particularly Ethiopia and South Africa, within the framework of the "China's One Belt One Road Initiative" (BRI) Project, which claims to enhance connectivity and economic cooperation between Asia, Europe, and Africa. It focuses on the period 1994 to 2019. The study draws on theories of international relations, interdependence, dependency and soft power to provide valuable insights into China's political and economic relationships with these two African countries. These theories offer a focused perspective, enabling us to explore the political and economic factors that underpin these bilateral relations. China's investments, infrastructure projects, loans, aid, and trade in Africa, especially in Ethiopia and South Africa, remain the key pillars of the asymmetrical nature of interdependence relations. It shows the sensitivity and vulnerability of these respective states and their economies and the trend toward greater dependency of African countries on China. China's relations with Ethiopia and South Africa have both successes and limitations. Ethiopia is highly dependent on China due to China's significant investments in the manufacturing and infrastructure sectors, which could lead to a debt trap due to a shortage of credit and loan opportunities from the World Bank, IMF, and Europe, as well as a trade deficit. South Africa, on the other hand, is less reliant on China due to its financial strength, but it is dependent on trade with China, which is dominated by exporting raw materials and importing finished goods, as well as China's public debt. Overall, China has strong interests in maintaining good relations with Africa, particularly Ethiopia and South Africa, for access to raw materials and agricultural products, a growing market for Chinese goods, and diplomatic influence and support, so it appears less reliant and more dominant in its mutual relations with these two African countries. In addition, Ethiopia and South Africa's political and economic significance within the broader context of the BRI provides China with an opportunity to deepen its relationships with Africa as a whole. On the other hand, solidarity and an equal relationship may begin to slip into dependence. Hence, this asymmetrical interdependence relationship may lead to an increasing trend toward dependence relationships due to China's rising economic influence and financial control over Ethiopia and South Africa.